Assessment of market waste as feedstock for biogas digester in Cape Coast – Ghana - Asiamah, Rhoda Donkor (University of Cape Coast, 2024)
With an expanding growth in the world’s population, there is an urgency to continually find alternative strategies to foster resourceful and sustainable waste treatment options. The availability and variety of potential feedstocks for biogas generation require reliable knowledge of the waste characteristics and evaluation of specific feedstock types. Even so, not all waste products are suitable for biotransformation. Also, an extensive range of market organic waste is underutilized, resulting in resource waste and other detrimental environmental issues. Consequently, there is an increasing focus on better feedstock utilization and reliability for improved biogas. This research seeks to assess market waste as a potential feedstock for biogas digesters. Using the purposive sampling technique, suitable organic wastes (eleven samples from each market) were weighed from three selected markets (based on proximity and the abundance of food and vegetable vendors) in Cape Coast to determine their abundance and reliability. The findings revealed the average total waste generation per week for each market to be 436.29 kg (Abura), 362.46 kg (Kotokuraba), and 140.64 kg (UCC Science) indicating the abundance of waste for bioconversion in Cape Coast. The waste characteristics showed considerable moisture content ranging from 57.44 % to 91.27 %. The TS with VS concentrations in the waste ranged from 8.73 % - 42.56 % and 0.17 % - 35.06 % respectively. The pH ranged from 3.19 - 6.13 Even though the waste had significant NPK Variation, it was ascertained that the organic fraction of municipal solid waste is typically poor in nutrients. The Cu and Zn determined in the study were 0.98 µg/g to 57.13 µg/g and 25.56 µg/g to 245.07 µg/g respectively. The waste had higher levels of BOD₅ (155.73 mg O₂/L to 731.89 mg O₂/L) and COD (2680 mg O₂/L to 28128) indicating high levels of pollutants in waste. It also had high pathogen contamination in waste samples highlighting a potential environmental and public health risk.
xiv, 132p;,ill.
Keywords: Anaerobic digestion; Feedstock; Organic fraction of municipal solid waste; Market waste; Waste (s)